PPO.26 Actim partus – the first year at St. Michael's Hospital, Bristol. (9th June 2014) - Hillman-Cooper, C; Ghag, K; Dempsey, A; Denbow, M; Lopez Bernal, A
Abstract : Introduction: Actim Partus use as a predictor of preterm labour in symptomatic women was audited. It was hoped that clinical outcomes would match anticipated efficacy and that Actim Partus would serve as a useful tool to determine antenatal steroids timing. Methods: Data collection was prospective and retrospective, using a standardised proforma. Women presenting (November 2011–November 2012) with threatened preterm labour necessitating an Actim Partus swab were included. A retrospective review of all women who had presented with "Abdominal Pain" was also undertaken, to ensure inclusion of all eligible women. Results: Total deliveries n = 5798. Preterm deliveries (23–35/40) n = 242. Actim Partus swabs performed (23–35/40) n = 182; 42% positive (n = 77), 58% negative (n = 105). Of the 77 positive swabs, 49% delivered preterm, 51% at term. Of 105 negative swabs, 91.5% delivered at term, 8.5% preterm. Test to delivery interval for swab positive women; 48% delivered >2 weeks. Of a total of 134 spontaneous preterm deliveries, 69% didn't have an Actim Partus performed prior to delivery, 24% had a positive swab history and 6% a negative swab history. Conclusion: Outcome data followed anticipated results. 48% of positive swabs delivered outside the 2 week interval, implying that antenatal steroids timing was not optimal for these women. 69% of spontaneous preterm deliveries occurred in women presenting in established labour, without prior Actim Partus assessment. This raises the fundamental question of the validity of this test as a mechanism for prediction of women at greatest risk of preterm labour.